ANALISIS DAN REDESAIN WEBSITE UNIVERSITAS PGRI RONGGOLAWE TUBAN MENGGUNAKAN METODE USER CENTERED DESIGN - Bashofi Bashofi; Tri Sagirani; I Gusti Ngurah Alit Widana Putra (Jurnal Sistem Informasi Universitas Dinamika, 2022)
: The Academic Information System (AIS) website is a web-based academic information system application with the aim of providing information about academics to students. With the AIS students can find out information related to campus academics such as student biographies, class forums, departmental curriculum, semester lectures, Study Plan Cards (SPC), class schedules, attendance, thesis, Study Results Cards (SRC), list of grades, transcripts , and finance. The results of interviews with Information Technology at PGRI Ronggolawe Tuban University that the number of visitors in September and February was due to guardianship by students who used the SIA application to view Study Plan Card (SPC) information. The results obtained from this study serve as recommendations for improving the user interface and user experience on the Academic Information System (AIS) website of the University of PGRI Ronggolawe Tuban. So that students can find information about lectures easily and with an easy-to-use interface design. From the results of the questionnaire, the improvement in the value of each indicator is Learnability 2.56, Efficiency 2.94, Memorability 2.31, Error 2.38, and Satisfaction 2.43. The final result of calculating the average for each indicator is a value of 2.52. According to the Likert scale from a value of 1-4 the value of 2.52 is in the good category.